2002
DOI: 10.1016/s0304-3959(01)00438-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic hyperalgesia versus painful hypoalgesia: two distinct mechanisms of neuropathic pain

Abstract: Patients with sensory disturbances of painful and non-painful character show distinct changes in touch and/or pain sensitivity. The patterns of sensory changes were compared to those of human surrogate models of neuropathic pain to assess the underlying mechanisms. We investigated 30 consecutive in-patients with dysaesthesia of various origins (peripheral, spinal, and brainstem lesions) and 15 healthy subjects. Tactile thresholds were determined with calibrated von Frey hairs (1.1mm). Thresholds and stimulus-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
139
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(144 citation statements)
references
References 54 publications
5
139
0
Order By: Relevance
“…Accordingly, patients with pain and hyperalgesia exhibit a nearly identical shift of stimulus-response function and incidence of hyperalgesia to stroking as normal subjects after capsaicin injection (9). These findings indicate that capsaicin-induced experimental hyperalgesia is a valid human surrogate model for neurogenic hyperalgesia, and support the view that central sensitization in neurogenic hyperalgesia is a feature of one group of neuropathic pain states (8,10).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Accordingly, patients with pain and hyperalgesia exhibit a nearly identical shift of stimulus-response function and incidence of hyperalgesia to stroking as normal subjects after capsaicin injection (9). These findings indicate that capsaicin-induced experimental hyperalgesia is a valid human surrogate model for neurogenic hyperalgesia, and support the view that central sensitization in neurogenic hyperalgesia is a feature of one group of neuropathic pain states (8,10).…”
supporting
confidence: 63%
“…It is characterized by two different clinical features: neurogenic hyperalgesia in patients with minor sensory impairment and painful hypoalgesia in patients with major sensory deficits (8). Central sensitization of nociceptive neurons in the spinal cord by primary nociceptive afferent input is the mechanism underlying neurogenic hyperalgesia during neuropatic pain.…”
mentioning
confidence: 99%
“…Additionally, secondary 12 changes in cortical and subcortical brain regions, triggered by cognitions, emotions 13 and attention may further add to central sensitization and development of spontaneous 14 activity and pain [40,41]. Another mechanism potentially contributing to 15 augmentation of central pain processing is deafferentation: Clinical and QST 16 examinations revealed deficits in large fibre function not only in group Denervation 17 but also in group Neuropathic Sensitization, indicating nerve fibre damage that for the 18 latter group may have induced secondary sensitization of higher order nociceptive 19 neurons [42]. QST findings from patients with other conditions thought to involve 20 central sensitization such as whiplash associated disorders [43], LBP [44] or 21 fibromyalgia [45] have also shown increased sensitivity to thermal and mechanical 22 pain stimuli consistent with findings in the present study.…”
Section: Discussion 19mentioning
confidence: 99%
“…In another study, Maihöfner et al 35 used fMRI to examine the cortical network involved in the processing of pin-prick hyperalgesia in patients with CRPS I, because pin-pricking is known to activate A␦ fibers. 36,37 Compared with nonpainful mechanical stimulation, during pin-prick hyperalgesia, there was a significantly increased activation of the S1 cortex contralaterally, S2 cortex bilaterally, insular cortex bilaterally, parietal association cortex (PA) contralaterally, inferior parietal lobule (IPL) bilater-ally, superior, middle, and inferior frontal cortex bilaterally, and the anterior cingulate cortex bilaterally. It was concluded that the cortical network underlying pin-prick hyperalgesia comprises areas involved in nociceptive, motor, and attention processing, which might account for a number of clinical symptoms occurring in CRPS.…”
Section: Somatosensory Systemmentioning
confidence: 99%